Non-Decreasing Economic Growth Rate of Inflation (NDEGRI) in light of empirical studies - Bednarczyk, Jan L.; Brzozowska-Rup, Katarzyna (Inflacja niespowalniająca wzrostu gospodarczego (NDEGRI) w świetle badań empirycznych, 2019)
The article presents the results of estimating economic growth depending on the inflation levels in selected countries. The results were obtained by means of regression splines, in particular, cubic splines and a B-spline curve. The method applied helps to identify both the area of Non- Decreasing Economic Growth Rate of Inflation and inflation for which the rate of growth reaches its maximum. The calculations and graphic presentations demonstrate that maximum rates of economic growth were reached in inflation ranges of 5%-15% for Poland and 3%-16% for the G-20 countries studied. The data analysis leads to the conclusion that central bank margins for their accommodative monetary policies in the studied countries can be wider than it is implied by the doctrinal bases of the inflation targeting policy or its more restrictive version – strict inflation targeting.
Econometrics = Ekonometria, 2019, Vol. 23, No. 1, s. 9-18
Keywords: low inflation trap; central banks inflation target; regression splines; pułapka niskiej inflacji; cel inflacyjny banku centralnego; regresja funkcji sklejanych